Intonation processing of interrogative words in Mandarin: an event-related potential study - Wang, Rui; Wang, Mengru; Georgiev, Georgi V. (Frontiers in Human Neuroscience, 2023)
Intonation is the variation in pitch used in speech, which forms the premise of tonal and non-tonal languages. Interrogative words are words that introduce questions. Previous research lacks clarity regarding the specific cues used in the processing of word intonation. To address this gap, this study used the event-related potential electroencephalogram (EEG) research method to explore the intonation processing of tone two (mid-rising) interrogative words in Mandarin. For this, the word “shui,” meaning “who,” was selected as the experimental material. To avoid the influence of the environment, gender, and semantics, the Hum version, corresponding to the stimulus material, was also adopted for the experiment. This study used a passive oddball paradigm to examine the clues of intonation information processing in automatic cognitive processing through amplitude, latency, time window, and evoked location potential mismatch negativity. The standard stimulus was the declarative intonation with a high probability of occurrence (90%), and the deviant stimulus was the interrogative intonation with a low probability of occurrence (10%). In the time window of 370–450 ms, the mismatch negativity was found at the F3, F4, C3, Cz, and C4 channels. The findings show that, in the passive oddball paradigm, lexical semantics are essential for intonation processing at the pre-attentive level, which is dominated by the frontal and central areas of the brain. The results support the functional and comprehensive hypotheses that the processing of intonation is based on the function of language and that bilateral regions are involved in this processing. This study makes an important contribution by providing event-related potential evidence that lexical semantics plays a key role in the pre-attentive processing of intonation, as shown by the significant differences between semantic and non-semantic conditions.